Analytical Modeling of Particle Scratching Process - Shouhong Chen; Mingjun Sun; Yuantao Fan; Fangchen Yin; Jixiang Huang; Shengui Huang (Applied Sciences)
This study develops a new physical and analytical model for the particle scratching process, where a particle is modeled as a sphere. It investigates the flow of workpiece material introduced by the particle’s motion, dividing the contact area into zones of elastic and plastic deformation. Forces applied to the particle in both zones are calculated, and parameters defining the extent of elastic rebound and plastic upheaval are introduced. The study also presents stress distribution in the plastic zone, discusses the factors influencing the force ratio, and reveals that the force ratio increases with greater elastic rebound, plastic upheaval, cutting depth, and strain strengthening, but decreases with larger particle sizes. Yield stress was found to have no effect on the force ratio. These findings will guide research in practical material processing as well as in scratch applications.